Persepsi Remaja Tentang Problematika Pernikahan Dalam Seris Mendua - Beta Kurnia; Vethy Octaviani; Sapta Sari (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Adolescence is a period of exploring self-potential to form a solid personality, teenagers will later experience marriage. Currently early marriage and infidelity is one of the factors causing divorce. With so many cases of divorce due to infidelity that occur based on true stories, the filmmakers made this story into a work through a media with the aim of being able to convey the moral message of the story of infidelity to the public, one of the series that was appointed, namely Series Mendua. Series Mendua tells about the problems of marriage. In this study, the researcher chose the perspective of adolescents as research subjects, so based on this background, the researcher raised the title "Youth Perceptions of Marriage Problems in the Double Series". The purpose of this study is to find out how adolescents perceive marital problems in the Mendua Series. This study used a qualitative descriptive method, and was analyzed based on the Hypodermic Needle theory. The results of the study show that the adolescent's perception of marital problems in the Mendua Series is a positive thing, namely a series that is accepted by society, provides lessons in running a household, with very professional roles. The average informant uses cellphone media, watches the telegram application. The message conveyed by Series Mendua in running a household is not to easily listen to other people's words, prove it to yourself if there is a problem and solve it immediately. Perceptions about Series Mendua that marriage is not only harmonious but also has marital problems such as infidelity, fights, domestic violence, lies, hatred and divorce.